Advantages of Milk in Light of Sunnah - Jalali, Sayed Mohammad (Journal of Social Sciences - Kabul University, 2025)
Milk is one of the blessings of Allah, essential for human development from infancy. During childhood, it serves as a primary source of nourishment, supporting growth and overall health. Even beyond infancy, Allah has permitted the consumption of milk from lawful animals such as camels, cows, and sheep for human benefit. This article first defines milk and then explores its advantages. While the benefits of milk are vast and could be discussed extensively, this study focuses specifically on its significance as mentioned in the Holy Quran and in the interpretations of renowned scholars. The article further references the hadiths of the Prophet Muhammad (peace be upon him) and explains their context based on authentic Islamic texts.